200k views
3 votes
How do u solve -18-6k=6 (1+3k)

User NeilK
by
5.8k points

2 Answers

5 votes
we can to ANYTHING to an equation as long as you do it to both sides

we can undistribuet a 6 on left
6(-3-k)=6(1+3k)
divide both sides by 6
-3-k=1+3k
add k both sides
-3=1+4k
minus 1 both sides
-4=4k
divide by 4
-1=k
User NickStoughton
by
5.5k points
3 votes
Let's solve your equation step-by-step.−18−6k=6(1+3k)

Step 1: Simplify both sides of the equation.
−186k=6(1+3k)
Simplify: (Show steps)6k−18=18k+6

Step 2: Subtract 18k from both sides.6k−1818k=18k+618k24k−18=6

Step 3: Add 18 to both sides.24k−18+18=6+1824k=24

Step 4: Divide both sides by -24.24k−24=24−24k=−1

Answer:k=1
User Msroot
by
5.9k points